Pathogenicity islands - Midolli Vieira, Mônica Aparecida (O Mundo da Saúde, 2009)
Pathogenicity island are inserted DNA fragments in the bacterial chromosome that confer a variety of virulence traits to the microorganisms. Among this variety of virulence properties we can SEE/: the ability of adhering and invading the host cells, toxins production, iron uptake and the synthesis of Type Three Secretion System, a molecular device that allows the effectors molecules translocation inside the host cells. The feature of acquiring virulence traits in one genetic event allows the formation of new pathogens, as well the pathogenic microorganism’s evolution.